Detection of damage in structural waveguides using high frequency waves - Ayala Castillo, Pedro Christian [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Wave propagation research for Structural Health Monitoring (SHM) has been increasing recently. It allows the detection of damage at its early stages of development. This dissertation describes a theoretical study of wave propagation for the purpose of detection and quantification of damage in a beam structure. Of particular interest is the way in which waves interact with damage that is symmetrical with respect to the neutral axis. An analysis of a one-dimensional structural waveguide incorporating a piezoelectric actuator and sensors in a pitch-catch and pulse-echo configuration is presented. The model is developed in the frequency domain, which is then transformed into the time domain using the inverse Fourier transform. This enables the effect of damage on wave propagation between the actuator and the sensor to be investigated in both the time and the frequency domains. The size of the actuator and the sensor, and the size of damage are investigated for a thin aluminum beam. It is shown that the time-domain approach is preferable to a frequency domain approach for damage detection in this kind of structure. It is found that longitudinal waves are more sensitive to a change in thickness for a symmetrical system and it is better to measure reflected rather than transmitted waves. Further, it is found that due to the dispersive nature of bending waves, it is possible in some situations for the reflected wave amplitude to decrease rather than increase as the beam thickness is reduced

Pesquisas em propagação de ondas para aplicação de monitoramento de integridade estrutural (SHM) tem tido um incremento considerável recentemente. Este procedimento permite detectar danos nas fases iniciais. Esta dissertação descreve um estudo teórico de propagação de ondas para o propósito de detecção e quantificação de dano em uma viga. De particular interesse é a maneira que as ondas interagem com o dano, considerado simétrico com respeito ao eixo neutro. Uma análise de uma estrutura unidimensional de ondas guiadas incorporando o atuador e sensores piezelétricos em configuração pitch-catch e pulse eco é apresentada. O modelo é desenvolvido no domínio da frequência e posteriormente transformado no domínio do tempo através da transformada de Fourier inversa. Isto permite que o efeito do dano entre o atuador e o sensor seja estudado no domínio do tempo e da frequência. Os comprimentos do atuador e do sensor e a profundidade do dano são estudados em uma viga de alumínio delgada. Mostra-se que uma abordagem no domínio do tempo é preferível em relação a abordagem no domínio da frequência para detecção e quantificação de danos na estrutura. Os resultados mostraram que ondas longitudinais são mais sensíveis a variação da espessura para um sistema simétrico e é melhor medir ondas refletidas que as transmitidas. Além disto, verificou-se que devido à natureza dispersiva das ondas de flexão é possível que em algumas situações a amplitude da onda refletida seja diminuída em vez de aumentar quando a espessura da viga é reduzida
Detecção de danos em estruturas guiadas usando ondas de alta frequência
Keywords: Localização de falhas (Engenharia); Testes não-destrutivos; Monitoramento da integridade estrutural; Structural health monitoring